Bella's bedspread : ladybird reading phonics book 12 - Ross, Mandy; Shearing, Leonie (Ladybird London, 2006)
A story which is designed to help beginner readers grasp the important link between sounds and the letters that represent them. This book presents a tale of a girl and her flying bedspread.